Statistical analyses of unidirectional static forces on instrumented rowing oarlocks - Laschowski, B.; Nolte, V. (Procedia Engineering, 2016)
The PowerLine System includes instrumented rowing oarlocks, which measure athlete-applied forces during on-water rowing. Despite its international popularity, limited research has considered the quality engineering of the PowerLine system. Accordingly, the following research examined the convergent validity and test-retest reliability of the PowerLine force measurements. Unidirectional static forces of up to 431N were applied to nine sweep and eight scull oarlocks over fifteen days of testing. The differences between the PowerLine force measurements and the known static forces were statistically analyzed. The PowerLine force measurements were consistent over the fifteen days of testing, but were 2.0% ? 0.8 percentage points less than the quantities of the known applied forces. Although the differences between the experimental measurements and known applied forces corresponded with the manufacturer's specifications, calibration factors for each PowerLine oarlock were generated to correct for the minor discrepancies.